2018
DOI: 10.1002/rcm.8268
|View full text |Cite
|
Sign up to set email alerts
|

Triple oxygen isotope analysis of nitrate using isotope exchange cavity ringdown laser spectroscopy

Abstract: The IE-CRDS method for determining Δ O values in nitrates utilizes a user-friendly and relatively cheaper benchtop analytical instrument, representing an alternative to IRMS-based methods for certain applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Here we further eliminate the possibility of oxygen isotopic exchange between nitrate and water in acid solution during the extraction process by estimating the δ 18 O value of the isotopically normal end‐member (Δ 17 O = 0‰). If oxygen isotopic exchange between nitrate and water occurred, an x axis intercept (Δ 17 O = 0‰) in the δ 18 O‐Δ 17 O scatter plot (Figure 5) should be close to the δ 18 O value of H 2 O used in this study (approximately –14‰), as shown in a H 2 O‐NO 3 − isotopic equilibrium experiment (Gazquez & Claire, 2018). The actual x axis intercept of 19‰ (Figure 5) suggests that the low Δ 17 O values observed in our study are not analytical artifacts.…”
Section: Resultssupporting
confidence: 68%
“…Here we further eliminate the possibility of oxygen isotopic exchange between nitrate and water in acid solution during the extraction process by estimating the δ 18 O value of the isotopically normal end‐member (Δ 17 O = 0‰). If oxygen isotopic exchange between nitrate and water occurred, an x axis intercept (Δ 17 O = 0‰) in the δ 18 O‐Δ 17 O scatter plot (Figure 5) should be close to the δ 18 O value of H 2 O used in this study (approximately –14‰), as shown in a H 2 O‐NO 3 − isotopic equilibrium experiment (Gazquez & Claire, 2018). The actual x axis intercept of 19‰ (Figure 5) suggests that the low Δ 17 O values observed in our study are not analytical artifacts.…”
Section: Resultssupporting
confidence: 68%
“…In addition to the demonstrated advantages, (1) the method has the potential to be adapted to δ 17 O analysis by online converting the oxygen in the benzyl nitrate to O 2 in a Au furnace, followed by IRMS analysis or to H 2 O after online isotopic equilibrium with NO 3 – , followed by CRDS analysis, , (2) the strategy to convert oxyanions to organic esters can also be easily extended to other oxyanions in natural samples, making the highly desirable simultaneous analysis of oxyanions as a mixture, a possibility, (3) the method is amenable to automation, (4) benzyl nitrate (and nitrite) can be analyzed for δ 15 N analysis on EA/Py/IRMS or GC/Py/GC/IRMS without any further workup, which compares favorably with a recent method where nitrate was converted to nitrobenzene for δ 15 N isotope analysis by GC/C/IRMS (note that 1/3 of the O in nitrate is lost during the conversion to nitrobenzene), and , (5) nitrite can also be derivatized with a similar conversion rate to that of nitrate under the same reaction conditions, with no observed mutual interferences between the two or interference from other coexisting ions (see Figure ). For simultaneous isotopic analysis of both nitrate and nitrite, the advantages of our method are clear as the problems of selective reduction of nitrate or conversions of nitrite to nitrate before bacterial reduction are avoided. , In the next paper of this series, we will report our results on realizing the above-listed potentials, in particular, (4) and (5).…”
Section: Discussionmentioning
confidence: 99%